ALDH1L2 orchestrates redox–growth coupling in renal carcinoma: pan-cancer evidence and mechanistic validation of the ROS–Akt/mTOR/S6K axis - Jiang, Chao; Liu, Songsong; Zhang, Liwen; Li, Shiji; Wang, Jinyou; Wang, Yi (Frontiers in Immunology, 2026)
BackgroundAldehyde dehydrogenase family 1 member L2 (ALDH1L2) has been relatively understudied in cancer. We aimed to systematically characterize its expression patterns, clinical significance, and potential functions across cancers and to validate its biological roles in urologic tumors.MethodsLeveraging The Cancer Genome Atlas pan-cancer resource, we profiled ALDH1L2 across tumor types with respect to expression patterns, clinical outcomes, genomic features, immune contexture, epigenetic associations, and indices of stemness and heterogeneity. Protein-level differences were examined by immunohistochemistry in bladder cancer (BLCA), prostate adenocarcinoma (PRAD), and kidney renal clear cell carcinoma (KIRC) tissues. To functionally interrogate ALDH1L2, we performed siRNA-mediated knockdown in relevant cell models and evaluated proliferation and motility-related phenotypes using wound-healing, Transwell, and EdU incorporation assays. In KIRC, Western blotting together with reactive oxygen species (ROS) detection was conducted to probe potential mechanistic links.ResultsALDH1L2 was differentially expressed in multiple cancers and significantly associated with overall and disease-specific survival in KIRC. IHC showed higher ALDH1L2 expression in KIRC tissues than in adjacent normal tissues, but lower expression in BLCA and PRAD. Functionally, ALDH1L2 knockdown suppressed proliferation and migration in KIRC cells, while promoting these processes in BLCA and PRAD cells. In KIRC, ALDH1L2 silencing increased ROS levels and reduced Akt/mTOR/S6K phosphorylation, consistent with decreased EdU incorporation.ConclusionThis study is the first to systematically untangle the divergent roles of ALDH1L2 in KIRC, BLCA, and PRAD from a pan-cancer perspective combined with ex vivo experiments, suggesting that ALDH1L2 may serve as an important molecule influencing tumor progression and the immune microenvironment, thereby providing a new potential target for the diagnosis and treatment of related cancers.